Effect of phosphorus levels on growth and yield of turmeric (Curcuma longa L.) - Ajit Kumar Singh, Rakesh Banwasi (Journal of Spices and Aromatic Crops, 2010)
A field experiment was conducted at Raigarh (Chattisgarh) to study the effect of five levels ofphosphorus (0, 50, 100, 150 and 200 kg P2O5 ha-1) on growth and yield of turmeric (Curcumalonga) (var. TCP-1). A common dose of N @ 150 kg ha-1 and K2O @ 120 kg ha-1 was applied inall the treatments. Application of phosphorus significantly influenced various growthcharacters and yield. The highest yield of fresh rhizome (156.3 q ha-1) was recorded withapplication of 150 kg P2O5 ha-1 followed by 149.2 and 147.9 ha-1 rhizomes with application of100 and 200 kg P2O5 ha-1, respectively. These treatments were significantly superior over othertreatments and on par with each other. However cost : benefit ratio was highest in thetreatment with application of 150 kg P2O5.